The Effect of Work Motivation and Work Discipline on Teachers’ Performance - Yudiar, Yudiar; Putra, Alhadi Yan; Fahmi, Muhammad (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the individual and combined influence of work motivation and work discipline on the performance of civil servant (ASN) teachers in public junior high schools across Palembang City. Employing a quantitative survey approach, data were collected from a sample of 103 ASN teachers. Work motivation was measured using Porter and Lawler’s theory, work discipline via Malayu S.P. Hasibuan’s indicators, and teacher performance was assessed based on PermenPAN-RB Number 6 of 2022. Data analysis was conducted using multiple linear regression in SPSS 26.0. The analysis revealed that work motivation has a positive and significant effect on teacher performance (regression coefficient = 0.360, t-value = 4.880, p-value = 0.000). Conversely, work discipline demonstrated a negative and insignificant effect (regression coefficient = -0.154, t-value = -1.697, p-value = 0.093). Simultaneously, both variables significantly influenced performance (F-value = 12.045, p-value = 0.000), with the model explaining 19.4% (R-squared = 0.194) of the variance in performance. This research provides a novel empirical contrast by simultaneously testing established motivational theory (Porter and Lawler) against a disciplinary framework (Hasibuan) within the specific context of Indonesian civil servant teachers, revealing the unexpected and paradoxical finding that discipline, as measured, may not positively correlate with performance. School administrators should prioritize strategies that enhance intrinsic and extrinsic motivation, such as recognition and career development opportunities. The findings suggest that traditional punitive approaches to enforcing discipline may be counterproductive; instead, a re-evaluation of disciplinary policies towards supportive and empowering frameworks is recommended. This study contributes to educational management literature by highlighting that motivation is a more potent driver of teacher performance than discipline in this context. It provides policymakers and school leaders with evidence-based insights to design more effective professional development and performance management systems that focus on motivational factors.